GAMBARAN PENDERITA INFEKSI LUKA OPERASI PADA PASIEN PASCA OPERASI BERSIH (CLEAN) DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE OKTOBER - DESEMEBER 2013 - Kurnia, Andy; Tripriadi, Effif Syofra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTSurgical site infection (SSI) is an infection caused by pathogenic microorganism that contaminate the surgical wound at the time of surgery or after surgery. SSI is the kind of healthcare-association infection or nosocomial infections (NI). This descriptive retrospective study explained the overview surgical site infection of post - clean surgical patients at Arifin Achmad General Hospital of Riau Province October to December 2013 period. The source of data was taken from medical records of clean surgical patient at Arifin Achmad General Hospital of Riau Province. In this study, a total of 192 patients were included into the clean surgical patients. The prevalence of surgical site infection in this study was 6.8 (13 patients). By the age group, the highest percentage of patients with post - clean surgical SSI was 41 - 60 years. By the sex, the comparison of patients with post – clean surgical SSI between men and women was 1.2 : 1. By the comorbidities, the highest percentage of patients with post – clean surgical SSI was the patients that have comorbidity non-diabetic. By the duration of surgical, the highest percentage of patients with post – clean surgical SSI was > 2 hours. By the length of stay, the highest percentage of patients with post – clean surgical SSI was > 7 days. By the prophylactic antibiotics administration, the highest percentage of patients with post – clean surgical SSI was clean surgical patients who not given prophylactic antibiotics. By the pre-operative procedure, shaving of the surgical area was pre-operative procedure that had highest percentage in patients with post – clean surgical SSI.Keywords: surgical site infection, clean surgical, patient overview.